Review Zerbino DD, Bagriy MM, Bodnar YaYa, Dibrova VA, editors. [Pathomorphology and histology: atlas]. Vinnitsa: New book, 2016. 800 p. Ukrainian. - Editorial office of journal "Morphologia" (Морфологія, 2016)
The atlas in a systematic order, based on modern positions, reflects the histological structure of tissues and organs, pathological findings of general pathological processes, cytopathology and pathomorphology of diseases of all systems, organs and tissues of the human body. All microphotographs are represented by the original histological and cytological preparations.